Perancangan Dan Pengembangan Website Sebagai Media Promosi Digital Marketing Edulink Menggunakan Cms Wordpress - Aris Fadly; suhada, Raihan Achmad Suhada; Diar Putri Yani; M Handika N; Dede Irsandi (JEKIN - Jurnal Teknik Informatika, 2025)
Abstract - Digital technology has become an essential part of educational development, supporting both teaching and learning processes and promoting educational services. Edulink, a digital education platform, offers various features to support educational activities. However, the challenge of increasing the platform's visibility and appeal remains a major issue. This study aims to design and develop a website as a digital marketing tool for Edulink using WordPress CMS. The development process applied the waterfall method, which includes stages such as analysis, design, implementation, and testing. The research resulted in the creation of the Edulink.id website as a digital marketing platform built using the Elementor plugin, enabling the development of attractive and functional web pages. System testing was conducted using the black box testing method to ensure that all features functioned as expected without examining the source code. The conclusion of this study highlights that the designed website provides an effective digital marketing solution and supports Edulink's marketing strategies to reach a broader audience in the education sector.